The Baptist Union of South Africa’s mission orientation needs transformation: A scrutiny by an insider - Lukwikilu C. Mangayi (HTS Teologiese Studies/Theological Studies, 2019)
This article aims to trigger a process of critical reflexive analysis relative to how colonial perspectives are played out in the contemporary mission orientation of the Baptist Union of South Africa (BUSA). It highlights the fact that the BUSA’ s mission orientation, predominantly evangelism and church planting, is still embedded in the colonial perspectives influenced by the thoughts of the 19th-century missiologists Henry Venn and Rufus Anderson. Hence, the key argument of this article is that the BUSA’s mission orientation should be released from these colonial perspectives in order to give way to the emergence of an authentic and contextual Baptist missional agency in South Africa. A scrutiny of the BUSA reveals that it faces threefold challenges, namely, historical, philosophical and methodological challenges. Failure to address these challenges has (1) robbed the BUSA of imagination to measure up to contemporary contextual issues, (2) made it predominantly otherworldly in worldview and mainly membership-centred in focus and (3) made it embrace and practice on the ground ‘missionary activist’ and ‘conversionist’ reductionist shortcuts. To move forward, the BUSA is called to go through continuous conversions and reflexive process as a prerequisite for a deep transformation experience. This article concludes by contributing three solutions, namely, generating new mission insights befitting the South African context should involve the collective, avoid missionary reductionist shortcuts by opting for an integrated and holistic mission praxis and embrace participatory action research as a way forward for BUSA’s mission agenda.